At the Beginning of Glorious Days Based on a Novel by Aleksey Tolstoy - Tolstoj, Aleksej Nikolaevic (RUSCICO, 2006)
In late 17th-century Russia, Czar Peter the Great orders an attack on Turkey, which refuses to pay taxes to the Russian government. The Russian military is equipped with outdated technology, and they suffer their first defeat. After the defeat the czar orders the building of a fleet, and sends many educated men to study in Germany, France, and Holland. Russian victory over Turkey will not only force the Turks to pay taxes, but also make the Sea of Azov accessible to the Russians. [en.wikipedia.org]